Efficacy of adjuvant cytokine-induced killer cell immunotherapy in patients with colorectal cancer after radical resection. (1st January 2020) - Pan, Qiu-Zhong; Zhao, Jing-Jing; Yang, Chao-Pin; Zhou, Yu-Qing; Lin, Jun-Zhong; Tang, Yan; Gu, Jia-Mei; Wang, Qi-Jing; Li, Yong-Qiang; He, Jia; Chen, Shi-Ping; Song, Meng-Jia; et al.
ABSTRACT: Adjuvant chemotherapy after surgery is the standard treatment modality for stage III and part of stage II or stage IV colorectal cancer (CRC) patients. However, the 5-year overall survival (OS) rate remains unsatisfactory. Thus, developing combination therapies is essential to improve the prognosis of patients with CRC. The present study aimed to determine the effect of a sequential combination of cytokine-induced killer cell (CIK) infusion and chemotherapy for patients with CRC. 122 patients with CRC treated with postoperative adjuvant chemotherapy were retrospectively included in this study. Among them, 62 patients received adjuvant chemotherapy only (control group), while the other 60 patients, with similar demographic and clinical characteristics, received adjuvant chemotherapy and sequential CIK cell immunotherapy (CIK group). Survival analysis showed significantly improved disease free survival (DFS) and OS rates in the CIK group compared with the control group (log-rank test, P = .0024; P = .008, respectively). Univariate and multivariate analyses indicated that sequential CIK cell treatment was an independent prognostic factor for patients' DFS and OS. Subgroup analyses showed that sequential CIK cell treatment significantly improved the DFS and OS of patients with high-risk T4 stage and insufficient chemotherapy duration. In conclusion, these data indicate that sequential adjuvant CIK cell treatment combined with chemotherapy is an effective therapeutic strategy to prevent disease recurrence and prolong survival of patients with CRC, particularly for patients with high-risk T4 stage and insufficient chemotherapy duration.